Life in Treaty Port China and Japan (Springer Singapore, 2018)
This edited volume moves beyond the traditional examination of the treaty ports of China and Japan as places of cultural interaction. It moves 'beyond the Bund', presenting instead the history of material culture, the everyday life of the residents of the treaty ports beyond the symbology of Shanghai's waterfront. Bringing for the first time together scholars of China and Japan, museum curators, legal, economic and architectural historians, it studies the treaty ports not only as sites of cultural exchange, but also as sites of social contestation, accommodation and mobility, covering topics as varied as day to day life itself, such as family, property and law, health and welfare, travel, visual culture and memory. The call of this volume is to peel the multiple layers of the encounter between East and West in the treaty ports of China and Japan.